Antigen of Haemophilus influenzae in bronchial tissue. Issue 9 (September 1981) - Clarke, C W; Hannant, C A; Scicchitano, R; Donald, K J; Jackson, B
Abstract : Haemophilus influenzae antigen was detected in five of seven bronchial biopsies obtained from patients undergoing diagnostic bronchoscopy. Antibody against H influenzae antigens was obtained from a patient with bronchiectasis. Immunofluorescent techniques were used. This provides further evidence to support the pathogenicity of H influenzae in lower respiratory tract disorders.